Constrains on dark matter cross section with standard model particles from the orbital period decay of binary pulsars - Lucero, Gonzalo Agustin (2024)
It is shown that the data from the orbital period decay of binary pulsars give strong constraints on the dark matter-nucleons cross section. The limits are robust and competitive because this new method for testing dark matter interactions with standard model particles has a minimal number of assumptions combined with the extremely high accuracy on the measurement of the decay rate of the orbital period of binary systems. Our results exclude (with 95% confidence) spin independent interactions with cross sections greater that 3.1x10-31 cm2 for a dark matter particle with mass mc2 = 1 keV and 3.7x10-31 cm2 for mc2= 1 TeV which improves by several orders of magnitude previous constraints.